Faktor – Faktor yang Mempengaruhi Status Gizi Pada Balita - Margarita Harvin Dwi Oktaviani; Agustina Sri Oktri Hastuti; Christina Ririn Widianti (STIKes Panti Rapih, 2022)
ABSTRACT Background: The malnutrition problem in Indonesia and foreign countries is still very concerning, there are still many children experiencing malnutrition. This phenomenon occurs because many factors affect the nutritional status of children under five, for example economic factors, diet, history of infectious diseases, and the lack of parental knowledge. Purpose: This literature review purposed to determine the effect of economic factors, diet, history of infectious diseases and parental knowledge. Methods: This literature review method was a narrative literature review, journals were obtained from five databases, namely Pubmed, Sage Journal, Science Direct, Google Scholar and Chocrane with time release between 2015 - 2020. Journal searches used PRISMA so that 5 journals were found discussing factors that influence nutritional status in toddlers. Results: This literature review showed that economic factors, diet, history of infectious diseases and parental knowledge greatly affected the nutritional status of children under five both in Indonesia and abroad. Conclusion: Economic factors affected the nutritional status of children under five, dietary factors affected the nutritional status of children under five, historical factors impacted the nutritional status of children under five and the knowledge of parents affected the nutritional status of toddlers. Keywords: factors, nutritional status, toddlers